Materiales didácticos y su impacto en el proceso de enseñanza – aprendizaje en el idioma inglés en los estudiantes de primer año de educación básica de la Unidad Educativa Jacinto Aspiazu Peralta - Zambrano Zambrano, Pedro Javier (2021)
The present research work was carried out at the “Jacinto Aspiazu Peralta” School located in the La Esperanza parish of the Quevedo canton. A study sought to establish the importance of using didactic materials for the discipline of English and their value as mediators among teachers, students and real life, specially designed for teaching-learning in first grade children. The objective of the research was based on the importance of correctly using didactic materials to improve the impact on the teaching process - learning in the English Language in the students of the First Year of Basic Education of the Educational Unit "Jacinto Aspiazu Peralta" Through interviews and surveys conducted with teachers and students, it was diagnosed that teachers did not use didactic material in their classes, creating shortcomings in the teaching-learning process resulting in poor academic performance in the English subject. In conclusion, it is necessary for teachers to become aware of the importance of the use of didactic materials within the English subject and thus have a greater positive impact on teaching-learning, and their application within the curricular plans.